Fresno County Young Lawyers Hopper Luncheon Keynoter California Supreme Court Associate Justice Malcolm Lucas - Watkins, Howard::::::::: (1985)
Justice Malcolm Lucas, Presiding Justice George Brown and Jim Christiansen at head table at Del Webb Plaza Ballroom